Revitalisasi Taman Merbabu berdasarkan Kebutuhan Masyarakat terhadap Ruang Terbuka Hijau melalui Komunikasi Non-verbal - Pratiwi, Elsa Intan; Sri Utami; Uzia, Wa Ode Ulfa; Fitriani (FAKULTAS TEKNIK UMKENDARI, 2024)
Global Warming is an issue issue in the implementation and efforts to create a green building. The greenhouse effect that causing global warming are increasingly standing tall. National and international development and international development that is not friendly to the environment needs to be to be considered. To address these issues, an organization called the World Green Building Council (WGBC) was established. an institution called the world green building council (WorildGBC), which is one of the estabilished members in Indonesia. one of its estabilished members is in Indonesia, namely the green building council Indonesia (GBCI). Green building assessment standards and guidelines issued by GBCI is a reference for use by people in Indonesia. The civil engineering and planning faculty building is a building that has been built for a long time. built, has a function as a faculty office on the first floor and a teaching and learning function on the second to fourth floors. teaching and learning functions on the second floor to the fourth floor. In the assessment using GBCI standards against the building, then the acquisition obtained is 42 assessment points, or a percentage of 35.90% and the predicate is bronze. To improve the bronze predicate to gold is the need for procurement and improvement that must be done. The procurement and improvements made to the six assessment categories.